Two-phase system and transition metal catalyzed reactions. - Falicki, Slawomir. (University of Ottawa (Canada), 1990)
The first examples of the application of biphasic and phase transfer catalysis to early-transition-metal organometallic chemistry are described. These include very efficient and convenient syntheses of the ($\eta\sp5$-cyclopentadienyl)tricarbonylhydridovanadate anion under remarkably mild biphasic conditions. The latter is capable of effecting, under phase transfer conditions, the reduction of halides, sterically encumbered nitro compounds, and the cyclodehydration of $\alpha,\beta$-unsaturated ketones. The reactions may proceed via electron transfer pathways. The use of nickel cyanide under biphasic or phase transfer conditions converts vinyl epoxides to the unsaturated ketones and/or unsaturated $\delta$-hydroxyacids. These results represent the first examples of the use of transition-metal complexes in catalytic-two-phase isomerization of vinyl epoxides. The key catalytic species is believed to be the cyanocarbonylnickel anion, participation of which has been proposed in the reaction mechanism. O-Benzyl oxime ethers were obtained in modest yields by the exposure of benzylic bromides to nitric oxide, a palladium(0) or ruthenium complex as the catalyst, aqueous sodium hydroxide, benzene as the organic phase and a quarternary ammonium salt as phase transfer agent. This provides the first example of a catalytic reaction of halides which involves free or co-ordinated nitric oxide and is also a novel process in the area of a phase transfer catalysis utilizing nitric oxide as a reactant.
Keywords: Chemistry, Inorganic.